Answering the right questions. Addressing biodiversity conservation in post-conflict Colombia (2020)
The post-conflict scenario in Colombia poses several environmental urgencies, making it necessary to identify and prioritize new challenges for biodiversity conservation and ecosystems management. It is critical to understand how government agencies, NGOs, and academics perceive these challenges, as they all contribute to fundamental decision-making on environmental issues. To achieve this objective we formulated fifty-two research questions that were edited, evaluated, and prioritized by members of each group in a dedicated workshop. Ten of these questions were identified as top priorities and shared with twenty additional members of each group. Perceptions and rankings of the ten priority questions were then compared among groups, but no statistical difference was found. These results highlight that broadly similar goals for biodiversity conservation are shared by all key decision makers in post-conflict Colombia. Namely, conservation through sustainable management practices and development of local economies previously affected by the conflict. The process of developing and prioritizing these research questions helped to identify key drivers of biodiversity loss and create a research agenda to mitigate environmental impacts in post-conflict Colombia.